2004
DOI: 10.1093/glycob/cwh135
|View full text |Cite
|
Sign up to set email alerts
|

TNF -induced insulin resistance in adipocytes as a membrane microdomain disorder: involvement of ganglioside GM3

Abstract: Membrane microdomains (lipid rafts) are now recognized as critical for proper compartmentalization of insulin signaling, but their role in the pathogenesis of insulin resistance has not been investigated. Detergent-resistant membrane microdomains (DRMs), isolated in the low-density fractions, are highly enriched in cholesterol, glycosphingolipids and various signaling molecules. Tumor necrosis factor alpha (TNFalpha) induces insulin resistance in type 2 diabetes, but its mechanism of action is not fully unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 47 publications
8
124
0
2
Order By: Relevance
“…2002), and excessive ganglioside content can disrupt insulin signaling by displacing the insulin receptor from these microdomains (Kabayama et al. 2004). Modifying dietary energy intake is a likely means to control glycosylated ceramide supply.…”
Section: Resultsmentioning
confidence: 99%
“…2002), and excessive ganglioside content can disrupt insulin signaling by displacing the insulin receptor from these microdomains (Kabayama et al. 2004). Modifying dietary energy intake is a likely means to control glycosylated ceramide supply.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we have recently found that cholesterol depletion, which disrupts lipid microdomains, reduces insulin receptor autophosphorylation by insulin in R28 retinal neurons (T.E.F., M.K., unpublished data). In addition, GM3 within microdomains (18) has been implicated in insulin resistance in response to TNF-␣ (15), and, conversely, mice deficient in GM3 synthase exhibit greater insulin sensitivity (21). Recent reports suggest that glycosphingolipids can also mediate apoptosis and cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…Simple glycosphingolipids, such as glucosyl and galactosylceramide (cerebrosides or monohexosylceramides), serve as building blocks for more complex glycosphingolipids, including sulfatides, globosides, and gangliosides. Recent reports (15)(16)(17)(18)(19)(20)(21) suggest that these glycosphingolipids can mediate apoptosis, insulin resistance, and cellular stress. In addition, altered sphingolipid and glycosphingolipid metabolism causes several retinal diseases.…”
mentioning
confidence: 99%
“…Among such molecules, the monosialodihexosylganglioside, GM3, whose abundance in lipid rafts has been documented by Simons and Ikonen [4], plays important roles in receptor functions and signal transduction [5], like for instance the suppression of the phosphorylation of the epidermal growth factor receptor [6,7] and insulin receptor [8,9] or the recognition of the influenza virus via its binding to the sialylgalactose structure of GM3 during the adsorption-fusion process [10]. Other experimental findings [11] indicate that the ganglioside GM3 blocks the cells proliferation induced by vascular endothelial growth factor (VEGF) and by the ganglioside GD1a, and it is also able to inhibit the linking between the urokinase plasminogen activator receptor (uPAR) and the integrin a 5 b 1 necessary for the migration of the endothelial cells [12].…”
Section: Introductionmentioning
confidence: 99%